An Integrative Proposed Model of Corporate Governance: The Corporate Governance Mechanisms Mediates the Relationship between Board Intellectual Capital and Corporate Performance - Pardis, Seyed Taghi; Sofian, Saudah; Abdullah, Dewi Fariha (International Journal of Economics and Financial Issues, 2016)
Corporate Governance (CG) foster dynamic economic growth, increase financing, reduces costs of capital, manage stakeholder interest which ultimately increase corporate performance (CP). Researchers have argued that employees must be inspired by CG practices to manage the conflicts of interest. There is a growing need for integrative model for CG, however the gaps are still exist in the literature on corporate governance mechanism (CGM) and their mediating role to influence the interlinkages between board intellectual capital (BIC) and CP. This study propose an integrative model CG by reviewing the literature CGM, prior models and relevant constructs of BIC, structures, process, and performance. This paper synthesizes the thinking arising from the review of previous literature and models of CG, and proposes an integrative research model. From the perspectives CG, this study argues that the new model should explore the relationship among BIC, CGM and CP. Keywords: Intellectual Capital, Corporate Governance, Performance JEL Classifications: G34; O16; O34